OPTIMALISASI PENGGUNAAN KESEPAKATAN KELAS UNTUK MENINGKATKAN KEDISIPLINAN SISWA KELAS III SDN 220 CEREKANG LUWU TIMUR - Samsul Buhari; Badruddin Kaddas; Erwin Nurdiansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Discipline is a fundamental foundation for developing students' character from the elementary school level, particularly during transitional stages such as Grade III, when students move from the lower grades to the upper grades. This study aimed to investigate how the optimization of classroom agreements could improve the discipline of third-grade students at SDN 220 Cerekang, East Luwu Regency. The study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, which was conducted in two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The research subjects were all third-grade students of SDN 220 Cerekang. Data were collected through observations, field notes, and documentation, and were analyzed using both qualitative descriptive and quantitative descriptive methods with percentage analysis. The findings revealed that the average achievement of students' discipline indicators in Cycle II reached 86.2%, exceeding the predetermined success criterion of 80%. Therefore, the research was concluded at the end of Cycle II because the expected target had been successfully achieved.